MINAT MELANJUTKAN STUDI AKUNTANSI SISWA KELAS XII PROGRAM STUDI AKUNTANSI SMK DI TUREN - Mahmudah, Nufidatul (JURNAL LENTERA BISNIS, 2025)
Students' interest in pursuing accounting studies at the higher education level is a crucial factor in the development of human resources in the fields of finance and business. This study aims to analyze the influence of students' perceptions and parental parenting styles on students' interest in continuing their accounting studies at university. A quantitative approach was used in this research, with twelfth-grade students from the Accounting Study Program at SMK Turen as respondents. Data were collected through questionnaires and analyzed using multiple linear regression techniques. The results showed that students' perceptions had a positive and significant effect on their interest in continuing accounting studies. On the other hand, parental parenting styles, as the second independent variable, did not influence students' interest in pursuing accounting education at the university level. Simultaneously, students' perceptions and parental parenting styles significantly contributed to students' interest in choosing accounting studies in higher education. These findings indicate that a good understanding of accounting, combined with optimal parental support, can enhance students' motivation to continue their education in this field. This study has implications for educators to improve engaging learning strategies and supportive parenting approaches to encourage more students to pursue accounting studies